HUBUNGAN APOE-4 DAN JENIS KELAMIN DENGAN FUNGSI BAHASA DAN MEMORI PADA LANSIA - Abigail Madeline; Yuda Turana; Yvonne Suzy Handajani (PERDOSNI, 2021)
Background: The APOE-4 allele, which globally has an estimated prevalence of 3-41%, is one of the strongestgenetic risk factors for Alzheimer’s disease dementia which generally has an early symptom of decreased memory functionAim: To determine the relationship between the APOE-4 gene and gender on cognitive function, especially languageand memory domains. Methods: This research is a descriptive-analytic study with a cross-sectional study design. Data collection was carriedout in September 2019. Respondents in this study were 97 elderly (aged ≥ 60 years). Data collection was carried outby filling out questionnaires and assessing cognitive function (using the Boston Naming Test with a cut-off value of <13 anddelayed free recall with a cut-off of <6, which shows impairment) and laboratory examination of the APOE-4 genotype.The data analysis test was performed using the Chi-square test. Results: It was found that the average age of the respondents was 66.78 years???? and most of them were female(72.2%). A total of 27.8% of respondents were found to have a positive APOE-4 gene. The percentage of impaired languageand memory functions was 24.7% and 46.4%. respectively. Based on data analysis, it was found that there was arelationship between the APOE-4 gene with language function (p = 0.004) and gender with language function (p = 0.014)and memory function (p = 0.042). Discussion: There is a significant relationship between the APOE-4 gene with language function and gender withlanguageand memory functions.